2009
DOI: 10.1007/s11274-009-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous bioaugmentation and its possible application to oil spills

Abstract: Bioaugmentation (BA) for oil spills is a much more promising technique than is biostimulation (BS). However, the effectiveness of BA is variable, because the survival and the xenobiotic-degrading ability of introduced microorganisms are highly dependent on environmental conditions. As an alternative, autochthonous bioaugmentation (ABA) is proposed to overcome these difficulties. The ABA method is like a ready-made BA technology. In ABA, microorganisms indigenous to the contaminated site or predicted contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…JC11 had lower lubricant-degrading activity in seawater than in NSW, which contained several nutrients. Hosokawa et al (2009) suggested that nutrients as well as other abiotic conditions such as oxygen and temperature should be optimized during autochothonous bioaugmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JC11 had lower lubricant-degrading activity in seawater than in NSW, which contained several nutrients. Hosokawa et al (2009) suggested that nutrients as well as other abiotic conditions such as oxygen and temperature should be optimized during autochothonous bioaugmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of a bioaugmentation approach is also varied according to location. Autochthonous bioaugmentation (ABA), which is the inoculation of oil-degrading microorganisms that were previously isolated from the contaminated site, is recommended because the added microorganisms will be highly enriched and adapted to the contaminated environment (Hosokawa et al, 2009). Consequently, this study aims to isolate lubricant-degrading microorganisms from Thai coastal areas as well as to apply a selected strain for removal of boat lubricant from seawater.…”
mentioning
confidence: 99%
“…Thus, in many cases, potentially degrading strains isolated from site A are not necessarily applicable to site B, and isolates, including genetically engineered microorganisms, that are effi cient hydrocarbons degraders under laboratory conditions, are not necessarily effective in situ [25]. Moreover, it is not easy to get public acceptance for introducing alien species to soil [11].…”
Section: Archives Of Environmental Protectionmentioning
confidence: 99%
“…In this method, indigenous microorganisms which are potentially capable of degrading oils and well-characterized from the contaminated sites or predicted contamination sites are used. This method has a number of advantages for the decontamination of oilpolluted land with shorter treatment time, greater potential efficiency, lower impact on the environment, and relative ease in obtaining public support (Hosokawa et al 2009). Iriomote and Con Dao islands are both predicted contamination sites locating on a busy maritime route which transported 15 million bbl/d in 2013 and supplies 83 percent of crude oil and oil products to Japan and East Asian countries (EIA 2014).…”
Section: Introductionmentioning
confidence: 99%